Experience and Perceptions of Chinese University Students Regarding the COVID-19 Pandemic: A Qualitative Analysis - Wu, Yijin; Yin, Gaohui; Zhang, Yichi (Frontiers in Public Health, 2022)
The COVID-19 pandemic has exerted a significant influence on university student’s learning, life and mental health. Using the method of inductive content analysis, this study examined the experience and perceptions of Chinese university students regarding the COVID-19 pandemic. 18 university students including seven males and eleven females were involved in this study. In this study, we identified five themes concerning experience and perceptions of Chinese university students regarding the COVID-19 pandemic, that is, emotional reactions toward the COVID-19 pandemic, the influence of the COVID-19 pandemic on the participant’s learning, the influence of the COVID-19 pandemic on the participant’s daily life, participants’ positive responses to the COVID-19 pandemic, and China’s moves towards the COVID-19 pandemic. This study elaborated on experience and perceptions of Chinese university students regarding the COVID-19 pandemic, which would provide us a better understanding of how university students perceive the COVID-19 pandemic and to what extent the COVID-19 pandemic has influenced their learning and daily lives.